A White South African Liberal as a Hostage to the Other: Reading J.M. Coetzee's Age of Iron through Levinas - JORDAAN, Eduard (Institutional Knowledge at Singapore Management University, 2005)
Having been struck by the Levinasian aspects of J.M. Coetzee's Age of Iron, this article tries to `reveal' Coetzee's novel as a Levinasian narration of how the other ruptures a specific subject's self-regarding egoism, leading the subject to take up its responsibility for the other. Throughout, the concreteness and realism of the novel is considered supplementary to the abstraction of Levinas's philosophical thought. It is demonstrated how the main character in Age of Iron, Elizabeth Curren, is confronted by the other as a face, has her right to be put into question by the other, experiences guilt for her usurpation of the place of the other, which becomes positive in her assuming responsibility for the other. In awakening to the other, Curren moves from a Heideggerean concern with her own death (she is dying of cancer) towards a Levinasian prioritising of the other's life over her own. Her coming into con- tact with the political violence and oppression of late 1980s South Africa adds to and focuses her expiation for the other.